Sistem Informasi Administrasi Pembayaran Dealer Carsentro Berbasis Web - Aries Budhi Kurniawan; Agus Ariawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The current advancements in information technology have brought significant benefits to the industrial world, particularly in the automotive sector. Website development in business and computer- based academic information system development are among the utilization of information technology. With information technology, Carsentro dealer data can be processed quickly and easily, enabling the presentation of accurate, fast, transparent, and efficient administrative information reports. The purpose of developing this system is to address existing issues in the old system by creating an administration information system for Carsentro dealer rental payment data. The implementation of a new system for Carsentro dealer data can improve record-keeping accountability, thus avoiding manual input recording errors that cannot be monitored by dealers renting space at Carsentro. In the development of this administrative information system, the data to be inputted includes information on when dealers joined the Carsentro ecosystem, the amount of monthly rental fee invoices, payment data, and dealer debt or receivables data. The software used is DBMS (Database Management System) MySql as the data storage medium, while programming languages such as PHP, CSS, JavaScript, and HTML are used for interface development. This aims to facilitate both users and administrators in managing data.